Palynological Study Of Pematang Formation Of Aman Trough, Central Sumatra Basin - Christina Ani Setyaningsih (Testing Center for Oil and Gas LEMIGAS, 2013)
The palynological study of Pematang Group of Aman Trough, Central Sumatra Basin is carried out To construct biostratigraphy of Pematang Group. The palynological analysis provide a zonal subdivision And bioevent identification as well as environment of depositional interpretation. The study uses cutting And core samples which were collected from wells namely Well A-1 and Well B-1. The age of the sediment Ranges from â€œnot older than Middle Eoceneâ€ to â€œnot younger than Oligoceneâ€. Top Oligocene age is Identified by the last occurrence of Meyeripollis naharkotensis whilst the base Oligocene is uncertain. The Eocene age is defined by the occurrence of Florschuetzia trilobata and supported by the last occurrence of Cicatricosisporites eocenicus. The environment is deposited in alluvial fan to proximal lacustrine during Eocene to Late Eocene, then, changed into deltaic marine in Late Oligocene. Interestingly, the studied Sediment lacks of lacustrine elements suggesting the disappearance of lake deposit. The studied wells can be Separated into 5 events which are applicable within the studied area, from older to younger age as follow: The LO of Cicatricosisporites eocenicus, the fresh water apparent, and the freshwater prominent, the first Significant backmangrove, and the LO of Meyeripollis naharkotensis.Â